AAV2 and AAV9 tropism and transgene expression in the mouse eye and major tissues after intravitreal and subretinal delivery - Koponen, Sanna; Kokki, Emmi; Tamminen, Toni; Ylä-Herttuala, Seppo (Frontiers in Drug Delivery, 2023)
The eye is an excellent target for gene therapy because of its anatomical features. Gene therapy to treat ocular disorders relies on efficient gene delivery and transgene expression in the target cells. The aim of this study was to compare the biodistribution and safety of two different AAV serotypes after intravitreal (IVT) and subretinal injections. AAV2 (1 x 10 12 vg/ml) and AAV9 (5 x 10 12 vg/ml) vectors expressing enhanced green fluorescent protein (EGFP) and AAV9-empty (6 x 10 11 vg/ml) vector were injected intravitreally or subretinally into both eyes of adult C57Bl/OlaHsd mice. Biodistribution of the viral vectors in the eye and off-target tissues was studied using qPCR. GFP expression was studied from cryosections and GFP transduction efficacy was verified using immunohistostaining for GFP. In addition, electroretinography (ERG) was used to assess the effect of vectors on retinal function. In addition to the eyes, viral vector copies were found in distant off-target tissues such as the liver, especially after AAV9-EGFP IVT and subretinal injection. AAV9-EGFP injections showed more GFP expression throughout the retina compared to AAV2-EGFP. AAV2-EGFP IVT showed transgene expression mainly in the ganglion cell layer whereas subretinal injection showed GFP expression in the retinal pigment epithelium. In addition, GFP was expressed at a moderate level in the liver after both injection routes of AAV9 and in small parts of the brain after all injection groups except AAV9empty. Lowered a-and b-amplitude values were seen in ERG in both scotopic and photopic experiments after AAV9-EGFP subretinal injection compared to all other groups. This study shows that intraocular injection of AAV2 and AAV9 transduces retinal cells. Although more efficient transduction of the retina negatively affects the retinal function and off-target transgene expression of AAV9 makes AAV2 a more suitable gene delivery vector to treat ocular disorders.